Associations between serum 25-hydroxyvitamin D, body mass index and body fat composition among Emirati population: Results from the UAE healthy future study - AlAnouti, Fatme; Ahmad, Amar Sabri; Wareth, Laila Abdel; Dhaheri, Ayesha Al; Oulhaj, Abderrahim; Junaibi, Abdulla Al; Naeemi, Abdullah Al; Hamiz, Aisha Al; Hosani, Ayesha Al; Zaabi, Eiman Al; Mezhal, Fatima; Maskari, Fatma Al; et al. (Frontiers in Endocrinology, 2022)
Objective: Vitamin D deficiency and insufficiency are highly prevalent among several populations across the globe. Numerous studies have shown a significant correlation between body-mass-index (BMI) and Vitamin D status, but these results differed according to ethnicity. Despite the abundance of sunshine throughout the year, vitamin D deficiency is prominent in the United Arab Emirates (UAE). In this study, we analyzed the UAE Healthy Future Study (UAEHFS) pilot data to investigate the association between serum 25-hydroxyvitamin D (25(OH)D) and % body fat (BF) composition as well as BMI. Material and Methods: Data from a total of 399 Emirati men and women aged ≥ 18 years were analyzed. Serum 25(OH)D and standard measures of weight and height were included in the analyses. Vitamin D deficiency was defined as serum 25(OH)D concentration<20 ng/ml. Multivariate quantile regression models were performed to explore the relationship between serum 25(OH)D levels and % BF composition and BMI correspondingly. Results: More than half of the study participants had vitamin D insufficiency (52.4%), and nearly a third had vitamin D deficiency (30.3%); while only 17.3% had optimal levels. A statistically significant negative association between serum 25(OH) D levels and % BF composition was observed at intermediate percentiles while a statistically significant negative association between serum 25(OH)D and BMI was only observed at the median (50th percentile). Conclusion: The study findings support the association between low serum 25(OH) D levels (low vitamin D status) and high % BF composition and high BMI among adult Emiratis. Further longitudinal data from the prospective UAEHFS could better elucidate the relationship between serum 25(OH) D levels, % BF composition, and BMI in the context of various health outcomes among this population.